Analysis of serum B cell‐activating factor from the tumor necrosis factor family (BAFF) and its soluble receptors in systemic lupus erythematosus. Issue 4 (21st April 2019) - Vincent, Fabien B; Kandane‐Rathnayake, Rangi; Koelmeyer, Rachel; Hoi, Alberta Y; Harris, James; Mackay, Fabienne; Morand, Eric F
Abstract: Objectives: To determine the presence and clinical associations of the soluble receptors of B cell‐activating factor from the tumor necrosis factor family (BAFF) in serum of patients with systemic lupus erythematosus (SLE). Methods: Serum BAFF and soluble BAFF receptor (sBAFF‐R) were quantified using ELISA, and soluble B cell maturation antigen (sBCMA) and transmembrane activator and cyclophilin ligand interactor (sTACI) by Luminex, in 87 SLE patients and 17 healthy controls (HC). Disease activity and organ damage were assessed using SLE Disease Activity Index 2000 (SLEDAI‐2K) and Systemic Lupus International Collaborating Clinics (SLICC) SLE Damage Index (SDI), respectively. Results: BAFF and all receptors were detectable in all serum samples. Serum sBCMA and sTACI, but not sBAFF‐R, were significantly higher in SLE than in HC. Serum BAFF was also increased in SLE, but this association was attenuated after adjusting for age and ethnicity. Increased serum BAFF was associated with flare and organ damage. Increased serum sBCMA was associated with the presence of anti‐dsDNA, but not with overall or organ‐specific disease activity, flare or organ damage. Neither sTACI nor sBAFF‐R was associated with any SLE clinical parameters in multivariable analysis. While serum BAFF correlated negatively with sBAFF‐R in HC, no statistically significant correlations were observed between BAFF and its receptors in SLE patients. Conclusion: Serum BAFF was associated with flare and organ damage independent of the presence of its soluble receptors. While sBCMA was associated with anti‐dsDNA positivity, other soluble BAFF receptors were not associated with SLE clinical indicators. Abstract : We found that serum soluble B cell maturation antigen (sBCMA) and transmembrane activator and cyclophilin ligand interactor (sTACI), but not BAFF receptor (sBAFF‐R), were significantly higher in systemic lupus erythematosus (SLE) patients than in healthy controls (HC). Serum B cell‐activating factor from the tumor necrosis factor family (BAFF) was associated with flare and organ damage independent of the presence of its soluble receptors. While sBCMA was associated with anti‐dsDNA positivity, other soluble BAFF receptors were not associated with SLE clinical indicators.